Keefektifan Metode Microskill Untuk Meningkatkan Kualitas Supervisi Klinik - Sunarko Sunarko; Ova Emilia; Harsono Mardiwiyoto (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2012)
Background: Clinical education requires competent supervisor to guide student. Supervisory competency should be trained and closely monitored to ensure quality learning process taking place. The aim of this study is to evaluate the effect of micro-skill supervisory model to improve the supervision quality among nursing student. Method: The research used quantitative approach with quasi experimental design. Subject consisted 91 students of the third year Nursing students at Magelang Health Polytechnic. Students were divided into two groups: intervention group (44 students) and control group (47 students) using purposive sampling. Research questionnaire consisted of 21 items which were derived from 5 micro skill domains was used. Intervention was supervision using micro-skill model during 2 weeks in a rotation of clinical practice.Results: There was no difference of quality clinical supervision was used in the control group while in experiment group the pre and post test score was significantly different. The experiment group had higher quality of supervision. The study showed that only 9 items showed significant improvement of supervision and 12 items did not show any improvement.Conclusion: Clinical teaching using micro skill model is more effective in improving the quality of nursing student clinical supervision compare to the conventional method.